Determination of pilus-islands profile and antibiotic susceptibility of Streptococcus agalactiae isolated from urine of pregnant women - Susan Panahi; Mohammad Bagher Khalili; Maryam Sadeh; Mahmood Vakili (Iranian Journal of Microbiology, 2023)
Background and Objectives: Group B Streptococcus (GBS) is one of the most important causes of neonatal diseases and postpartum fever. GBS infection can be transmitted from the infected mother to her baby during delivery. This bacterium is also involved in causing urinary tract infections and asymptomatic bacteriuria, pyelonephritis, cystitis and urethritis. In addition to capsule, Pilus is known as a virulence factor of GBS. The aim of this study was to evaluate the frequency of pilus islands and antibiotic resistance in GBS isolated from urine of pregnant women in Yazd, Iran. Materials and Methods: In this cross-sectional study, 33 GBS samples isolated from the urine of pregnant women were studied by the multiplex polymerase chain reaction (PCR) method for the presence of pilus islands PI-1, PI-2a and PI-2b. Antibiotic resistance phenotype of tetracycline, penicillin, gentamicin, erythromycin, levofloxacin and clindamycin was determined by disk diffusion method. Data were analyzed using SPSS, version 16. Results: PI-1+PI-2a was the most frequent pilus island in the GBS isolates 28 (84.8%) and the frequency of PI-2b was 5 (15.2%). The frequency of PI-1+PI-2a was 50% in serotype III and 25%, 14.3%, 7.1% and 3.6% in serotypes Ia, II, Ib and V respectively (P=0.492). The sensitivity of all GBS isolates to penicillin was 93.9% and highest resistance to tetracycline (97%), clindamycin (24.2%) and erythromycin (21.2%). Conclusion: Most of the GBS urine isolates examined carried the PI-1+PI-2a gene, which increases bacterial potency in colonization and resistance to the immune system. Penicillin was best choice for prevention.